The Principle of Tax Justice and its Challenges in QRIS-Based Digital Economic Transactions - Lilisen Lilisen; Ainul Masruroh; Anto Kustanto (Lex Publica, 2026)
The rapid expansion of QRIS-based digital transactions has reshaped Indonesia’s payment ecosystem and integrated electronic transaction data into tax administration. This transformation enhances fiscal efficiency and transparency but raises concerns about tax justice, proportionality, legal certainty, and taxpayer rights. Existing studies emphasize modernization and revenue optimization, yet the normative implications of QRIS for justice remain underexplored. This study applies a normative legal method using statutory, conceptual, and analytical approaches to evaluate juridical dynamics of QRIS-based taxation. Findings reveal three issues: first, regulations prioritize efficiency and supervision over proportional burdens; second, disparities arise from inconsistent frameworks and unequal treatment of digital versus conventional actors; third, taxpayer rights are vulnerable due to limited safeguards for privacy, fairness, and certainty. The study contributes to adaptive digital tax law by stressing regulatory harmonization that balances efficiency with proportionality, equality, and protection of taxpayer rights.